Optimization of In-Plant Logistics Through a New Hybrid Algorithm for the Capacitated Vehicle Routing Problem with Heterogeneous Fleet - Kulaç, Seçil; Kazancı, Nevra (Sakarya University, 2024)
The vehicle routing problem (VRP) is a crucial group of transportation problems, and the traditional capacitated VRP (CVRP) directly handles external logistics with a homogeneous vehicle fleet. This study examines CVRP from the perspective of in-plant logistics, focusing on a heterogeneous fleet within an automotive factory. The homogeneous and heterogeneous vehicle fleets were compared to address the factory’s actual in-plant logistics issues. First, simulated annealing (SA), tabu search (TS) algorithms, and mathematical modeling were used. A hybrid approach was proposed, and all the proposed meta-heuristic algorithms were evaluated for homogeneous and heterogeneous vehicle fleets. According to the results, the reduction rates of fleet area and distribution costs using CVRP with heterogeneous fleets are 17% and 36%, respectively. In addition, to examine the effect of the hybrid algorithm parameters on the results, the traveling distance was calculated for different scenarios, and multiple regression analyses were performed. According to the multiple regression analysis, the hybrid algorithm's most affected parameter was the cooling coefficient. © 2024, Sakarya University. All rights reserved.
Keywords: Capacitated vehicle routing problem; In-plant logistics; Simulated annealing algorithm; Tabu search algorithm